การจัดการเรียนรู้แบบประสบการณ์ทางการพยาบาล - เสือพูมี นงนุช; นาคศรีสังข์ วัลทณี; สิงหเสม ประไพพิศ (Nursing Journal of The Ministry of Public Health, 2017)
บทคัดย่อ บทความนี้กล่าวถึงความสำคัญและแนวทางการจัดการเรียนรู้แบบประสบการณ์ทางการพยาบาล กล่าวคือ อาจารย์ผู้สอนควรคำนึงถึง ความแตกต่างระหว่างบุคคล ความยืดหยุ่นและศักยภาพในการเรียนรู้ของนักศึกษา เพื่อให้สอดรับการเปลี่ยนแปลงของรูปแบบการสอนในปัจจุบัน ด้วยวิธีการผสมผสานความรู้เดิมกับประสบการณ์ในรูปแบบที่ใหม่และแตกต่างกันออกไป โดยนำทฤษฏีการเรียนรู้แบบประสบการณ์มาใช้ในการพัฒนานักศึกษาให้เกิดผลลัพธ์การเรียนรู้ตามมาตรฐานคุณวุฒิระดับปริญญาตรี สาขาพยาบาลศาสตร์ ได้แก่ คุณธรรมจริยธรรม ความรู้ ทักษะทางปัญญา ทักษะความสัมพันธ์ระหว่างบุคคลและความรับผิดชอบ ทักษะการสื่อสารและการใช้เทคโนโลยีสารสนเทศ รวมทั้งทักษะทางวิชาชีพ และทำให้ผู้เรียนเกิดความพึงพอใจในการเรียนและมีแรงจูงใจในการเรียนมากขึ้น นำไปสู่ผลสัมฤทธิ์ทางการเรียนที่สูงขึ้น Management of Experiential Learning in Nursing Education. Nongnuch Suapumee* Wantanee Naksrisang* Prapaipis Singhasem** Abstract This article discusses the importance of and approach to the management of experiential learning in nursing. From experiential learning perspectives, the instructor should take into consideration individualized differences, flexibility and competence in the learning of students to meet the changes of the current teaching model. Furthermore, a combination of students’ current knowledge and new and various experiences should be set based on experiential learning theory. This teaching method can be beneficial in various ways. First, it can improve nursing students’ learning outcomes based on the six domains of the Thai Qualifications Framework of Bachelor’s degree Nursing Science program including ethical and moral development, knowledge, cognitive skills, interpersonal skill and responsibility, communication and information technological skills, and nursing professional skills. Second, it can promote learning satisfaction and motivation of the students. All these benefits will lead to greater achievement of nursing students.